2022
DOI: 10.3390/insects13040355
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Population Responses of Nilaparvata lugens after Feeding on Drought-Stressed Rice

Abstract: Drought stress greatly impacts insect development and population growth. Some studies have demonstrated increased reproductive capacity in drought-stressed insects; however, physiological changes in the brown planthopper (BPH), Nilaparvata lugens (Stål), during periods of drought are unclear. In this study, BPH fed on drought- stressed rice had lower population numbers than BPH feeding on non-stressed rice. Water content, osmotic pressure of hemolymph and total amino acid content of BPH were significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed that BPH infestation can regulate signalling pathways mediated by JA, SA, ethylene, ABA and H 2 O 2 in rice; these pathways in turn cause changes in metabolomes in rice and thus regulate the resistance of rice to BPH (Hu et al, 2016; Lou et al, 2013; Lu et al, 2014; Muduli et al, 2021; Zhang et al, 2021; Zhou et al, 2009). On the other hand, abiotic stresses, such as cold and drought, influence the performance of BPH directly and indirectly by affecting the physiological and biochemical status of rice plants (Horgan et al, 2021; Huang et al, 2017; Liang et al, 2022; Quais et al, 2020). Moreover, OsDREB1A is reported to promote the tolerance of rice to cold, drought and salinity stress (Ito et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that BPH infestation can regulate signalling pathways mediated by JA, SA, ethylene, ABA and H 2 O 2 in rice; these pathways in turn cause changes in metabolomes in rice and thus regulate the resistance of rice to BPH (Hu et al, 2016; Lou et al, 2013; Lu et al, 2014; Muduli et al, 2021; Zhang et al, 2021; Zhou et al, 2009). On the other hand, abiotic stresses, such as cold and drought, influence the performance of BPH directly and indirectly by affecting the physiological and biochemical status of rice plants (Horgan et al, 2021; Huang et al, 2017; Liang et al, 2022; Quais et al, 2020). Moreover, OsDREB1A is reported to promote the tolerance of rice to cold, drought and salinity stress (Ito et al, 2006).…”
Section: Introductionmentioning
confidence: 99%